1986
DOI: 10.1128/mcb.6.11.4093
|View full text |Cite
|
Sign up to set email alerts
|

Sequences involved in accurate and efficient transcription of human c-myc genes microinjected into frog oocytes.

Abstract: By microinjecting a series of deletion mutant constructs into Xenopus laevis oocytes, transcriptional control regions, two promoters, of the human c-myc gene were defined. In the case of the first promoter, sequences between -60 and -37 relative to the transcription start site contained an element essential for promoter activity. In the case of the second promoter, sequences between -66 and -56 relative to the initiation site appeared to be involved in accurate and efficient transcription. In both cases, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

1987
1987
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
1
23
0
2
Order By: Relevance
“…Thus, even though the episomal constructs have established different nucleosomal structures upstream of the P2 promoter in different cell lines, all constructs showed similar extents of paused pol II at the P2 promoter. The finding that pol II can bind efficiently to the P2 promoter in MA76 cells in the presence of nucleosomes 3 and 4 suggests that sequences of the P2 core promoter extending from Ϫ70 to ϩ50 might be sufficient to bind pol II not only in vitro and in transient transfection experiments (20,43) but also when c-myc is stably transfected and assembled in chromatin. Within this region of the c-myc promoter, the ME1a1, ME1a2, and E2F transcription factor binding sites have been found (4,20,38,71).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even though the episomal constructs have established different nucleosomal structures upstream of the P2 promoter in different cell lines, all constructs showed similar extents of paused pol II at the P2 promoter. The finding that pol II can bind efficiently to the P2 promoter in MA76 cells in the presence of nucleosomes 3 and 4 suggests that sequences of the P2 core promoter extending from Ϫ70 to ϩ50 might be sufficient to bind pol II not only in vitro and in transient transfection experiments (20,43) but also when c-myc is stably transfected and assembled in chromatin. Within this region of the c-myc promoter, the ME1a1, ME1a2, and E2F transcription factor binding sites have been found (4,20,38,71).…”
Section: Discussionmentioning
confidence: 99%
“…Sequences between -60 and -37 relative to the human c-myc P1 start site are essential for its activity in microinjected Xenopus laevis oocytes (48). Sequences between -101 and -353 relative to P1 have been reported to possess both positive (37) and negative (19) effector activity on the human c-myc P1 and P2 start sites.…”
Section: Tcccctgtaccgccacatcgcgtacttggctggcaacttcgaagtcatcctgccagtcccmentioning
confidence: 99%
“…The sequence of MBP-1 does not contain any known DNA-binding motifs such as a zinc finger structure (25,43), leucine zipper (32), POU-specific regions (11,15,(64)(65)(66), or homeoboxes (33,40,42 Several groups have investigated the sequence requirement for initiation at the P1 and P2 start sites of the human c-myc gene (10,19,37,48,59). Sequences between -60 and -37 relative to the human c-myc P1 start site are essential for its activity in microinjected Xenopus laevis oocytes (48).…”
Section: Tcccctgtaccgccacatcgcgtacttggctggcaacttcgaagtcatcctgccagtcccmentioning
confidence: 99%
“…1). A recent report of microinjection experiments with MYC deletion constructs into frog oocytes suggested that Spl should bind to this particular sequence and mediate the observed transcriptional activity (Nishikura 1986). Using in vitro gel retardation assays, we could not obtain any evidence for the binding of Sp 1 to f-mycP2.…”
Section: Analogy In Binding Specificities Of the Myc Promoter Fragmenmentioning
confidence: 99%